Making sense of genetic risk: A qualitative focus-group study of healthy participants in genomic research. Issue 3 (March 2018) - Viberg Johansson, Jennifer; Segerdahl, Pär; Ugander, Ulrika Hösterey; Hansson, Mats G.; Langenskiöld, Sophie
Highlights: The likelihood of the disease is not always informative for research participants. Research participants tend to understand genetic risk as a binary concept. Participants make sense of risk in the midst of their lives, which unfold in time. Risk communication may be enhanced by tailoring the communication to the participants' own lay conceptions. Abstract: Objective: It is well known that research participants want to receive genetic risk information that is about high risks, serious diseases and potential preventive measures. The aim of this study was to explore, by qualitative means, something less well known: how do healthy research participants themselves make sense of genetic risk information? Method: A phenomenographic approach was chosen to explore research participants' understanding and assessment of genetic risk. We conducted four focus-group (N = 16) interviews with participants in a research programme designed to identify biomarkers for cardiopulmonary disease. Results: Among the research participants, we found four ways of understanding genetic risk: as a binary concept, as an explanation, as revealing who I am (knowledge of oneself) and as affecting life ahead. Conclusion: Research participants tend to understand genetic risk as a binary concept. This does not necessarily imply a misunderstanding of, or an irrational approach to, genetic risk. Rather, it may have a heuristic function in decision-making. Practical implications: Risk communication may be enhanced by tailoring the communication to the participants' own lay conceptions. For example, researchers and counselors should address risk in binary terms, maybe looking out for how individual participants search for threshold figures.